Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper focuses on a steady increase in current account surpluses in 'Surplus 3' countries-Germany, the Netherlands, and Switzerland-since the mid-1990s. In Germany and the Netherlands, nonfinancial corporations seem to be behind the rising surpluses. In these countries, increasing corporate profits have not been converted into dividends, keeping a lid on consumption. In Switzerland, household savings seem to explain the bulk of the current account surplus: both mandatory and voluntary savings have been on an increasing trend since 2000. Trending net contributions to pension funds since 2000 and rising equity contribution for housing purchases are likely drivers.